2008
DOI: 10.1083/jcb.200805049
|View full text |Cite
|
Sign up to set email alerts
|

Fast regulation of AP-1 activity through interaction of lamin A/C, ERK1/2, and c-Fos at the nuclear envelope

Abstract: Sequestration of c-Fos at the nuclear envelope (NE) through interaction with A-type lamins suppresses AP-1–dependent transcription. We show here that c-Fos accumulation within the extraction-resistant nuclear fraction (ERNF) and its interaction with lamin A are reduced and enhanced by gain-of and loss-of ERK1/2 activity, respectively. Moreover, hindering ERK1/2-dependent phosphorylation of c-Fos attenuates its release from the ERNF induced by serum and promotes its interaction with lamin A. Accordingly, serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
163
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(171 citation statements)
references
References 62 publications
5
163
0
2
Order By: Relevance
“…Plasmids and siRNAs-pCMV-3V-c-Fos, pCMV-4A-c-Fos, and full-length HBXIP constructs were previously described (6,27,28). To identify the corresponding domain that activates c-Fos, full-length HBXIP was divided into 4 fragments, including amino acids 1-82, 83-173, 83-144, and 145-173.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasmids and siRNAs-pCMV-3V-c-Fos, pCMV-4A-c-Fos, and full-length HBXIP constructs were previously described (6,27,28). To identify the corresponding domain that activates c-Fos, full-length HBXIP was divided into 4 fragments, including amino acids 1-82, 83-173, 83-144, and 145-173.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence Staining and Confocal MicroscopyCells were grown on acid-treated glass coverslips as described elsewhere (27). Treated cells were fixed with ice-cold 4% paraformaldehyde for 10 min, washed three times with phosphatebuffered saline (PBS), and permeabilized with 0.1% Triton X-100 in PBS for 20 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[75] Interestingly, ERK functions within the nucleus may also be compartmentalized further: ERKs interact with lamin A at the nuclear envelope to promote rapid, mitogen-dependent AP-1 activation, by releasing cFos from its inhibitory interaction with lamin A. [76] A place for a scaffold…”
Section: Some Space For Erksmentioning
confidence: 99%
“…Recent evidence suggests that A-type lamins play a dynamic role in regulating signal transduction, particularly ERK1/2 signaling (1,(3)(4)(5). We previously showed that activated ERK1/2 in hearts of Lmna H222P/H222P mice, a mouse model of LMNA cardiomyopathy, contributes to disease (6 -8).…”
mentioning
confidence: 99%